A Case Study of Adjacency Pairs in Conversation of a Group of Arab Students in Informal Setting - Alkhaza’leh, Bilal (International Journal of Linguistics and Translation Studies, 2022)
Language is usually seen as a social phenomenon; there is a reciprocal relationship between language and society. When people use language, they do more than just try to get another person to understand the speaker’s thoughts and feelings. The current study aimed to analyze short conversation by group of Arab postgraduate students in informal setting with more focus on adjacency pairs’ sequences. The objectives of the study are to analyze the potential adjacency pairs by Arab speakers and find out the reasons of using such pairs. Data were collected and transcribed first in Arabic then translated to English using qualitative research methodology. The approach that has been chosen for this research is qualitative approach. In this context, the conversation occurred during informal setting that is in conversation and usual chatting setting among the friends. The speakers are from different Arabic countries. However they are very close friends since they are neighbors and meet each other frequently. Results showed that speakers violated the sequence of adjacency pairs; this might be due to the solidarity and affinity among them. The adjacency pairs found in this conversations are Greeting-greeting, turn taking, overlapping, Question-Answer, repetition, closing.